Advances in Natural Language Processing, Intelligent Informatics and Smart Technology Selected Revised Papers from the Eleventh International Symposium on Natural Language Processing (SNLP-2016) and the First Workshop in Intelligent Informatics and Smart Technology, 10-12 February 2016, Phranakhon, Si Ayutthaya, Thailand - Theeramunkong, Thanaruk; Kongkachandra, Rachada; Supnithi, Thepchai; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book constitutes the thoroughly refereed proceedings of the Eleventh International Symposium on Natural Language Processing (SNLP-2016), held in Phranakhon Si Ayutthaya, Thailand on February 10-12, 2016. The SNLP promotes research in natural language processing and related fields, and provides a unique opportunity for researchers, professionals and practitioners to discuss various current and advanced issues of interest in NLP. The 2016 symposium was expanded to include the First Workshop in Intelligent Informatics and Smart Technology. Of the 66 high-quality papers accepted, this book presents twelve from the Symposium on Natural Language Processing track and ten from the Workshop in Intelligent Informatics and Smart Technology track (SSAI: Special Session on Artificial Intelligence).
Semi-Automatic Framework for Generating RDF Dataset from Open Data -- Design for a Listening Learner Corpus for a Listenability Measurement Method -- The Effect of Automatic Tagging using Multilingual Metadata for Image Retrieval -- The NECTEC 2015 Thai Open-Domain Automatic Speech Recognition System -- Eye Region Detection in Fatigue Monitoring for the Military using AdaBoost Algorithm -- The Feature Extraction of ECG Signal in Myocardial Infarction Patients -- The Algorithm of Static Hand Gesture Recognition using Rule-Based Classification -- Medical Instructional Media in Human Body Systems using 3D Projection Mapping -- Development of Electromagnetic Wave Propagation in Microstrip Antenna using the Novel Finite Element Method -- Detection of Diabetic Retinopathy using Image Processing.
Keywords: Computational intelligence; Artificial intelligence; Computational linguistics; Computational Intelligence; Artificial Intelligence; Computational Linguistics